Ultrasmall PEI-Decorated Bi2Se3 Nanodots as a Multifunctional Theranostic Nanoplatform for in vivo CT Imaging-Guided Cancer Photothermal Therapy - Peng Zhang; Lei Wang; Xiuying Chen; Xiang Li; Qinghai Yuan (Frontiers Media S.A., 2021)
Bi-based nanomaterials, such as Bi2Se3, play an important part in biomedicine, such as photothermal therapy (PTT) and computed tomography (CT) imaging. Polyethylenimine (PEI)-modified ultrasmall Bi2Se3 nanodots were prepared using an ultrafast synthetic method at room temperature (25°C). Bi2Se3 nanodots exhibited superior CT imaging performance, and could be used as effective photothermal reagents owing to their broad absorption in the ultraviolet-visible-near infrared region. Under irradiation at 808 nm, PEI-Bi2Se3 nanodots exhibited excellent photothermal-conversion efficiency of up to 41.3%. Good biocompatibility and significant tumor-ablation capabilities were demonstrated in vitro and in vivo. These results revealed that PEI-Bi2Se3 nanodots are safe and a good nanotheranostic platform for CT imaging-guided PTT of cancer.